Photonic force optical coherence elastography for three-dimensional mechanical microscopy - Nichaluk Leartprapun (Nature Portfolio, 2018)
Optical tweezers, while well suited for micro-manipulation, are difficult to apply to volumetric microrheology. Here, Leartprapun et al. combine low-NA optical radiation-pressure forces with sensitive interferometric detection to enable volumetric microrheology with promising applications in biological systems.